Efek DMR terhadap Kemampuan Matematis Peserta Didik - Dinda Pratiwi, Dona; Rinaldi, Achi; Melinda, Selva; Nadila, Nadila (CV. Creative Tugu Pena, 2024)
This research aims to evaluate the impact of the DMR model on students' mathematical representation, reasoning and reversible thinking abilities. This research uses a quasi-experimental design with a posttest only control design. The population consisted of class Data was collected through description tests and analyzed using normality, homogeneity and Multivariate Analysis of Variance (Manova) tests. Manova results show that students who use the DMR model have better mathematical representation, reasoning and reversible thinking abilities compared to students who use the conventional model (direct instruction). Therefore, the DMR model is suitable for use in the classroom learning process. The DMR learning model can be considered as an alternative choice for training students' mathematical representation, reasoning and reversible thinking abilities. Keywords: DMR, Representation, Reasoning, Reversible Thinking